Integrating Padlet into Genre-Based Writing Instruction to Improve Students’ Writing Skills (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates the effectiveness of integrating Padlet into Genre-Based Writing Instruction (GBA) to improve students’ writing skills. Writing is a fundamental skill in English language learning, yet many students face difficulties in organizing ideas, using appropriate vocabulary, and applying accurate grammar and mechanics. A mixed-methods design was employed involving 35 eleventh-grade students at SMAN 7 Bandar Lampung. Quantitative data were collected through pre-tests and post-tests of descriptive writing, assessed using Jacobs et al.’s (1981) rubric. Inter-rater reliability showed excellent agreement (pretest r = .962; post-test r = .963), and normality assumptions were met. The mean pretest scores (Rater 1 = 52.02; Rater 2 = 51.69) increased substantially in the post-test (Rater 1 = 86.66; Rater 2 = 86.26), with a paired sample t-test confirming significant improvement (p < .05). Qualitative data from semi-structured interviews revealed three themes: (1) challenges in using Padlet (technical issues, adaptation, and low confidence), (2) positive influence on idea organization and writing development, and (3) suggested improvements in scaffolding and technical support. Overall, Padlet-supported GBA not only enhanced students’ descriptive writing performance but also fostered engagement, collaboration, and independent learning. This study contributes to the growing body of research on digital integration in genre-based pedagogy and offers pedagogical implications for promoting effective writing instruction in secondary education.